Gastrointestinal adverse reaction to food (GARF) and endoscopic confocal laser endomicroscopy (eCLE) - Frieling, Thomas; Gjini, Besmir; Melchior, Ilka; Euler, Philipp; Kreysel, Christian; Kalde, Sigrid; Krummen, Britta; Kiesslich, Ralf; Hemmerlein, Bernhard (Zeitschrift für Gastroenterologie, 2024)
Background and study aims Gastrointestinal adverse reaction to food (GARF) is reported frequently in the general population and even more in patients with disorders of the gut brain axis. However, there is a significant difference between self-reported and objective proven GARF. The aim of the study was to characterize a mucosal correlate of GARF by endoscopic confocal laser endomicroscopy (eCLE) with duodenal food challenge (DFC).Patients and methods In an observational and proof of concept study we evaluated 71 patients with disorders of the gut brain axis without (group I, n=19) and with (group II, n=52) GARF by eCLE and DFC. Spontaneous and food induced transfer of fluorescein into duodenal lumen was detected 10 minutes following intravenously application of fluorescein and 10 minutes after DFC.Results According to Rom IV, the patients (group I/II) could be classified as irritable bowel syndrome (IBS) 32%/31%, functional abdominal pain without changes in bowel movement 47 %/48 %, functional abdominal bloating/distension 0 %/10 %, functional diarrhea 5 %/ 2 %, and unspecified functional bowel disorder 16 %/10 %, respectively. 21 %/27 % of the patients responded with a fluorescein leakage into the duodenal lumen before and 74 %/69 % following to DFC. Frequency rank order of food components that induced a response were soy (55.5 %/60 %), wheat (60 %/45.5 %), egg (35.7 %/8.3), milk (30 %/18.2 %) and yeast (10 %/6.6 %), respectively. Histology of duodenal biopsies, number, form and distribution of intraepithelial lymphocytes and mucosal mast cells as well as mast cell function were normal. Overall, 14 %/79 % reported main symptom benefit following a food exclusion therapy according to eCLE and DFC that was significant different between the groups.Conclusion The results of our study indicate that eCLE with DFC is a technique to clinically evaluate patients with disorders of the gut brain axis and GARF resulting in a high proportion of patients reporting symptom benefit upon food exclusion dietary advice focussed on the results of eCLE.
Keywords: Endoscopic confocal laser endomicroscopy (eCLE); gastrointestinal adverse reaction to food (GARF); food intolerance; functional abdominal pain; irritable bowel syndrome (IBS); disorders of gut brain axis; intestinal permeability